Dynamics in urban state housing production: reflections on space formation - Schmidt , Lisandro Pezzi; Silva, Márcia da (Revista Cerrados, 2020)
The multiple strategies for social housing production and market alter the functional and also social structure of urban space. The articulation of the real estate developers, the state movement and the growing demand for the units, besides expanding the real estate business through spaces for capital circulation, arouses the need for reflection on the interests where the projects are located. The general objective of this research is to reflect on how the movement and production favors the formation of spatialities within the production of the Minha Casa Minha Vida Program (PMCMV). For the construction of the analysis it was necessary to combine several sources, which were systematized in order to cross the theoretical contributions and observation in the field and information derived from the choice of projects aimed at Track 1 - Condominium Systems in PMCMV. It should be noted that the research aims to contribute to the verticalization of studies on medium and small cities and will allow following and updating discussions on sectoral policies. It can be used to evaluate the structure and municipal management and how the social function of the city has been performed.